2022
DOI: 10.1186/s13287-022-03198-z
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation does not change the performance and characteristics of allogenic mesenchymal stem cells highly over-expressing a cytoplasmic therapeutic transgene for cancer treatment

Abstract: Background Mesenchymal stem cells (MSCs) driven gene directed enzyme prodrug therapy is a promising approach to deliver therapeutic agents to target heterogenous solid tumours. To democratize such a therapy, cryopreservation along with cold chain transportation is an essential part of the logistical process and supply chain. Previously, we have successfully engineered MSCs by a non-viral DNA transfection approach for prolonged and exceptionally high expression of the fused transgene cytosine de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…Trilineage differentiation ability of MSCs (i.e., adipogenic, osteogenic, and chondrogenic) is another criterion of the International Society for Cellular Therapy (ISCT) guide for defining MSCs ( 61 ). In agreement with our results using FucMSCs, previous work evaluated the effects of cryopreservation on the differentiation potential of MSCs after thawing, concluding that, although some results are controversial, cryopreservation does not alter MSC osteogenic, adipogenic or chondrogenic differentiation potential (data not shown) ( 56 , 62 65 ). In addition, previous studies from our group showed that fucosylated murine and human MSCs are able to efficiently differentiate into adipocyte, osteoblast and chondroblast cell lineages ( 20 , 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…Trilineage differentiation ability of MSCs (i.e., adipogenic, osteogenic, and chondrogenic) is another criterion of the International Society for Cellular Therapy (ISCT) guide for defining MSCs ( 61 ). In agreement with our results using FucMSCs, previous work evaluated the effects of cryopreservation on the differentiation potential of MSCs after thawing, concluding that, although some results are controversial, cryopreservation does not alter MSC osteogenic, adipogenic or chondrogenic differentiation potential (data not shown) ( 56 , 62 65 ). In addition, previous studies from our group showed that fucosylated murine and human MSCs are able to efficiently differentiate into adipocyte, osteoblast and chondroblast cell lineages ( 20 , 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we confirmed that porcine MNs can be preserved for 2 years using proper storage procedures. Cell cryopreservation studies have shown that canine and human adipose tissues, platelets, pancreatic cells [8][9][10][11][12], and even small organs, such as rat kidneys, can be cryopreserved [13]. Although intracellular ice crystal formation presents a challenge in the cryopreservation process, it can be averted by adequate immersion in a suitable freezing solution and replacement of water content.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a highly efficient cationic polymer-based transfection method to engineer MSCs to express a therapeutic transgene—cytosine deaminase uracil phosphoribosyl-transferase fused to a green fluorescent protein (GFP) reporter. These engineered cells showed strong anti-cancer potency in in-vitro, in subcutaneous laboratory models [ 20 , 26 ] and in companion animals with naturally occurring cancers [ 27 ]. The non-toxic prodrug (5-flucytosine, 5FC) is converted by CD into 5-flurouracil (5FU) that disrupts the nucleotide biosynthesis, leading to apoptosis [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%